INFLUENCE OF THE STYLE OF PEDAGOGICAL COMMUNICATION ON THE MOTIVATION AND LEARNING ACTIVITY OF ADOLESCENT CHILDREN - Fozilov Jakhongir Ibrokhimovich; Topvoldiyeva Zuxraxon Ravshan qizi; Abduraxmonova Mohinur Furqatjon qizi (American Journals, 2022)
INFLUENCE OF THE STYLE OF PEDAGOGICAL COMMUNICATION ON THE MOTIVATION AND LEARNING ACTIVITY OF ADOLESCENT CHILDREN